A new method for comprehensive utilization of wood vinegar by distillation and liquid−liquid extraction. (December 2018) - Li, Zhanchao; Zhang, Lening; Chen, Guanyu; Wu, Lijie; Liu, Boyang; Li, Yue; Sun, Shuang; Zhang, Hanqi; Zhang, Zhiquan; Wang, Ziming
Graphical abstract: Highlights: The work provided a method for comprehensive utilization of wood vinegar (WV). EtOAc/ n -Hexane (7/3, v/v) and pH = 4 were preferred for isolation of antioxidants. Acetic acid made inhibitory effect on antioxidant activity of phenolic compounds. The fraction enriched with acetic acid exhibited high antimicrobial activity. Abstract: To increase the added value and commercialization of wood vinegar (WV), a new method for comprehensive utilization of WV was developed. The primary distillation, liquid–liquid extraction and secondary distillation were used to isolate the different active fractions from WV in the new route. The antioxidant activities of all the fractions were expressed as vitamin C equivalent antioxidant capacities in mg/L using 1, 1-diphenyl-2-picrylhydrazyl scavenging assay, and the antimicrobial activities against Escherichia coli ( E. coli ) in vitro were represented by the absorbance at a wavelength of 600 nm. The results demonstrated that the isolation of the antioxidants (phenolic compounds) from the residue obtained from primary distillation was satisfactory when the EtOAc/ n -hexane (7/3, v/v) was used as extraction solvent and pH value was 4. Acetic acid has inhibition effect on the antioxidant activities of phenolic compounds. The fraction enriched with acetic acid exhibited high antimicrobial activity. Considering the low environmental risk of WV, the findings suggest that WV is potentially useful for the developments of antioxidant and antimicrobial agents in the field of medicine or food preservation and safety.